Ethics and Rationing Access to Dialysis in Resource‐Limited Settings: The Consequences of Refusing a Renal Transplant in the South African State Sector. Issue 3 (22nd June 2014) - Etheredge, Harriet; Paget, Graham
Abstract: Resource constraints in developing countries compel policy makers to ration the provision of healthcare services. This article examines one such set of Guidelines: A patient dialysing in the state sector in South Africa may not refuse renal transplantation when a kidney becomes available. Refusal of transplantation can lead to exclusion from the state‐funded dialysis programme. This Guideline is legally acceptable as related to Constitutional stipulations which allow for rationing healthcare resources in South Africa. Evaluating the ethical merit of the Guideline, and exploring the ethical dilemma it poses, proves a more complex task. We examine the actions of healthcare professionals as constrained by the Guideline. From a best interests framework, we argue that in these circumstances directing patient decision making (pressurising a patient to undergo renal transplantation) is not necessarily unethical or unacceptably paternalistic. We then scrutinise the guideline itself through several different ethical 'lenses'. Here, we argue that bioethics does not provide a definitive answer as to the moral merit of rationing dialysis under these circumstances, however it can be considered just in this context. We conclude by examining a potential pitfall of the Guideline: Unwilling transplant recipients may not comply with immunosuppressive medication, which raises questions for policies based on resource management and rationing.